(3edMeI eQJHI Ydi GdCTgQ GdQhejI aj GdMce Ydi GdcSha hGdNSha dOGfjGd GdfHi (B( (3Ydjg GdSdGe(B)s
(3ChdgG (B:s
(3gPg edMeI eQJHI Ydi GdGTgQ GdQhejI ai GdMce Ydi GdcSha hGdNSha hGdQYO hGdHQb hGfbVGV GdchGcH s
(3BNQgG (B:s
(3jbUO LgI GdeTQb hjchf HCQV GdHdbGA MQhH cKjQI EPG QeJ YQaGf GdCgdIhGHOC HQL MdJ GdTeS YfO hcGf GdaQGZ s
(3HgG fXGe GdJYbjHIs
(3HCWQGa ChQGbgG JbWjY GPgH HYV SWhQgGs
(3cJHJ Hbde ajg VHW hCNWGDgG TGFYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs